Mater rixarum?: Verträge des Staates mit jüdischen und muslimischen Religionsgemeinschaften - Lutz-Bachmann, Julia Katharina (Jus Ecclesiasticum, 2016)
Contracts between the state and churches are an old and well-proven instrument for coordination all of their rights and interests. They serve to disentagle but also to harmonize these institutions, which were originally enmeshed and of equal rank. Recently contracts with Jewish and of late with Islamic communities as well have been presenting new challenges. Julia Lutz-Bachmann analyzes these from the perspective of constitutional law.